2014
DOI: 10.1080/09297049.2014.906569
|View full text |Cite
|
Sign up to set email alerts
|

Multigroup confirmatory factor analysis and structural invariance with age of the Behavior Rating Inventory of Executive Function (BRIEF)—French version

Abstract: The parent and teacher forms of the French version of the Behavioral Rating Inventory of Executive Function (BRIEF) were used to evaluate executive function in everyday life in a large sample of healthy children (N = 951) aged between 5 and 18. Several psychometric methods were applied, with a view to providing clinicians with tools for score interpretation. The parent and teacher forms of the BRIEF were acceptably reliable. Demographic variables (such as age and gender) were found to influence the BRIEF score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
2
20
0
3
Order By: Relevance
“…Cross-sectional studies have shown a decrease in reported EF problems with increasing age. 51,52 A previous longitudinal study of our group showed a slight increase with age of BRI scores for children born preterm but not for term controls. 1 Another limitation of our study is that we only used parental reports of behavioral EF.…”
Section: Socialmentioning
confidence: 63%
“…Cross-sectional studies have shown a decrease in reported EF problems with increasing age. 51,52 A previous longitudinal study of our group showed a slight increase with age of BRI scores for children born preterm but not for term controls. 1 Another limitation of our study is that we only used parental reports of behavioral EF.…”
Section: Socialmentioning
confidence: 63%
“…First, several of the scales on the BRIEF, the most widely used behavioral rating measure of EF in developmental samples, have no parallel cognitive tasks, making empirical relationships between these two measurement approaches less likely (Toplak et al, ). Confirmatory factor analysis (CFA) has indicated that behavioral rating data obtained from the BRIEF coalesces around three higher‐order factors, metacognition, emotional regulation, and behavioral regulation, rather than reflecting the eight clinical scales or the metacognition index and behavioral regulation index (Egeland & Fallmyr, ; Fournet et al, ; Gioia, Isquith, Retzlaff, & Espy, ; Little et al, ). Similarly, EC was originally believed to consist of three distinct, but interrelated, abilities as measured by separate subscales: (a) Attentional Control ‐ the ability to voluntarily focus and shift attention, as well as disengage from alternative sources of attention using cognitive distraction; (b) Inhibitory Control ‐ the ability to inhibit contextually inappropriate behavioral responses; and (c) Activation Control ‐ the capacity to undertake an action when there is a strong tendency to avoid it (Eisenberg, Smith, Sadovsky, & Spinrad, ; Putnam et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…three-factor solution Comparative Fit Index [CFI]=.96, Adjusted Goodness-of-Fit Index [AGFI]=.81, Root Mean Squared Error of Approximation [RMSEA]=.14). More recently, Fournet and colleagues (2015) similarly examined fit of serial CFA models in a larger sample of typically developing French children ( N = 951) used to provide normative data for the translated parent-report BRIEF. Consistent with findings from Egeland and Fallmyr, the nine-scale, three-factor solution (BRI, ERI, MI) in these data appeared to be the best-fitting model relative to nine-scale one-factor and two-factor models and eight-scale models with one to three latent factors (Fournet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the Behavior Rating Inventory of Executive Function, Second Edition (BRIEF2; Gioia, Isquith, Guy, & Kenworthy, 2015), now contains nine scales and three factors (consistent with Egeland & Fallmyr, 2010; Fournet et al, 2015), with the Inhibit and Self-Monitor scales comprising the Behavior Regulation Index (BRI), the Shift and Emotional Control scales comprising the new Emotional Regulation Index (ERI), and the Initiate, Working Memory, Plan/Organize, Task-Monitor, and Organization of Materials scales comprising the Cognitive Regulation Index (CRI; the renamed Metacognitive Index). The removal of the Shift and Emotional Control scales from the BRI and addition of the Self-Monitor scale to this index suggests that prior work examining the internal structure of the measure no longer applies and new examinations of the measure are needed to support utility of the revised measure and its proposed scale alignment and interpretive guidelines.…”
Section: Introductionmentioning
confidence: 99%